Foreign ownership and its effects on employment and wages: The case of Sweden - Runar Brännlund; Jonas Nordström; Jesper Stage; Dick Svedin (IZA Journal of European Labor Studies, 2016)
In this paper, we study how foreign ownership of Swedish companies affects employment and wages. To study these effects, we specify a model based on the assumption that the Swedish labour market can be described as one where trade unions and employers bargain over employment and wages. Our hypothesis is that bargaining power is affected by institutional settings and the ownership of the firm. To test our hypothesis, we used a panel data set of 242 large Swedish manufacturing firms over the period 1980-2005. The results indicate no significant impact of foreign ownership on employment or wages in Sweden.
Keywords: J30; J50; D21; C33; 330; Bargaining power; Trade union; Employment; Wages